ICT Utilization in Teaching Islamic and Arabic Language and its Relation to Student Learning - Sinsuat-Imam, Bai Rojana (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the utilization of Information and Communication Technology (ICT) in the teaching and learning process of Islamic Studies and Arabic Language (ISAL) education in the Bangsamoro Autonomous Region in Muslim Mindanao (BARMM). The study aimed to determine the level of ICT competencies among teachers, assess the extent of ICT integration in instructional delivery, identify challenges affecting ICT implementation, and examine the relationship between ICT utilization and student learning outcomes. Guided by the concepts of technology integration in education, the study employed a quantitative descriptive-correlational research design using survey questionnaires as the primary data-gathering instrument. Respondents included ISAL teachers from selected educational institutions in BARMM. Data were analyzed using appropriate statistical tools to determine levels, relationships, and significant findings related to ICT utilization in ISAL education. The findings revealed that teachers generally demonstrated adequate ICT competencies and positively perceived the role of ICT in improving classroom instruction, student participation, comprehension, motivation, and overall learning engagement. The study also found that the effectiveness of ICT integration depended on the availability of ICT facilities, stable internet connectivity, institutional support, stakeholder involvement, and continuous teacher training. Furthermore, positive relationships were identified between teachers’ ICT competencies, access to technological resources, and improved instructional effectiveness and student learning outcomes. However, challenges such as limited infrastructure, inadequate technological resources, inconsistent internet access, and insufficient training opportunities constrained the full implementation of ICT in ISAL education. The study concluded that ICT utilization significantly enhances the quality of teaching and learning in ISAL education when supported by adequate infrastructure, institutional commitment, and teacher capability development. It recommended continuous ICT training programs, improved technological resources, enhanced internet connectivity, and stronger stakeholder collaboration to support effective ICT integration in educational institutions. This study supports Sustainable Development Goal (SDG) 4 on Quality Education by promoting inclusive and effective learning through technology integration. It also relates to SDG 9 on Industry, Innovation, and Infrastructure through the improvement of educational technological resources and digital learning systems. The sustainability impact of the study lies in strengthening institutional educational practices, improving digital teaching competencies, and supporting long-term educational development and accessibility in BARMM communities.
Keywords: Arabic Language; BARMM; ICT Competencies; ICT Integration; Islamic Studies; Learning Outcomes; Stakeholder Support; Teacher Training; Technological Resources